In vivo immunoamplifying effects of di-(2-ethylhexyl) phthalate on cytokine response. (February 2013) - Tanaka, Michitaka; Inoue, Ken-ichiro; Momoi, Takashi; Takano, Hirohisa
<x xml:space="preserve">Abstract</x> A recent epidemiological study has revealed the positive association between atopy morbidity in children and phthalate esters, environmental chemicals in house dust. Nonetheless, experimental and molecular evidences regarding the correlation between phthalates and allergic response/pathophysiology are not fully investigated. Among phthalate esters, di-(2-ethylhexyl) phthalate (DEHP) has been widely used for flexible polyvinyl chloride products including vinyl flooring and wall covering. In the present study, we examined the effects of exposure to DEHP on allergen (ovalbumin: OVA) -induced peritonitis in ICR mice. Repeated administration of OVA via intraperitoneal route induced peritoneal inflammation characterized by infiltration of granulocytes (neutrophils and eosinophils) into the cavity. DEHP synergistically exaggerated the OVA-related neutrophilic inflammation. Furthermore, DEHP + OVA profoundly amplified OVA-elicited inflammation- and allergy-related molecules such as interleukin-5, eotaxin, and keratinocyte-derived chemoattractant production/release in the peritoneal cavity. Taken together, DEHP aggravated OVA-related peritoneal inflammation, which is concomitant with local enhanced production/release of inflammation- and allergy-related molecules.